2002
DOI: 10.1002/1522-2683(200209)23:18<3168::aid-elps3168>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

A protein molecular weight map of ES2 clear cell ovarian carcinoma cells using a two-dimensional liquid separations/mass mapping technique

Abstract: A molecular weight map of the protein content of ES2 human clear cell ovarian carcinoma cells has been produced using a two-dimensional (2-D) liquid separations/mass mapping technique. This method uses a 2-D liquid separation of proteins from whole cell lysates coupled on-line to an electrospray ionization-time of flight (ESI-TOF) mass spectrometer to map the accurate intact molecular weight (M(r)) of the protein content of the cells. The two separation dimensions involve the use of liquid isoelectric focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…A saturated CHCA in 50% acetonitrile and 1% TFA was diluted to a 1:4 ratio (v/v) in 50% acetonitrile and 1% TFA. Angiotensin I, ACTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and ACTH (18-39) were added to the 1:4 diluted matrix solution. The resulting matrix-standard solution was vortexed.…”
Section: Maldi Sample Preparation-mentioning
confidence: 99%
See 1 more Smart Citation
“…A saturated CHCA in 50% acetonitrile and 1% TFA was diluted to a 1:4 ratio (v/v) in 50% acetonitrile and 1% TFA. Angiotensin I, ACTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and ACTH (18-39) were added to the 1:4 diluted matrix solution. The resulting matrix-standard solution was vortexed.…”
Section: Maldi Sample Preparation-mentioning
confidence: 99%
“…They also have the drawback of embedding the proteins of interest in a polyacrylamide gel, which necessitates awkward recovery and purification steps if subsequent analytical methods are to be applied downstream. In order to overcome these difficulties we have developed a 2-D liquid phase protein separation method that greatly facilitates the mapping of the protein content of human cells [10,11]. The method is based upon pI separation in the first dimension and non-porous RP-HPLC in the second dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, optimizing the average resolution (R avg ) for all peak pairs is much more important. The experimental average resolution for a mixture of n components is defined by: (8) By inserting the fundamental definition of resolution for a given pair of solute i and i+1 into eq 8 (t R and W are the retention time and baseline peak width): (9) and assuming a constant peak width of W avg under gradient conditions, we can show that: (10) By comparing eq 10 with eqs 6 and 7, it is clear that the average resolution is proportional to the peak capacity computed via eq 7: (11) Thus, optimizing the peak capacity (n c **) is equivalent to optimizing the average resolution. In this paper, we first study the effect of the individual operational variables (gradient time, flow rate, temperature and final eluent strength) on the peak capacity (n c **) of peptides for a fixed column format (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For bacteria, Fenselau's team showed that identification of small B. cereus proteins could act as potential markers for infectious spores (e.g., anthrax; 22). Lubman and co-workers have applied isoelectric focusing and RPLC, ESI/TOF, and offline tryptic digestion to identify proteins and PTMs from human cancers (49). Together, these approaches hold the promise of nearly 100% reliability (high predictive value) for earlier detection of complex diseases or drug efficacy.…”
Section: Biomarker Identification Without Digestionmentioning
confidence: 99%